2012
DOI: 10.1108/17542731211226754
|View full text |Cite
|
Sign up to set email alerts
|

Six Sigma and leadership: some observations and agenda for future research

Abstract: PurposeLeadership has for a long time been a topic that attracts the attention of both academics and practitioners. In spite of the extensive literature on leadership and very little literature on leadership in Six Sigma, there is almost a complete absence to explain how and what leadership characteristics are needed for successful implementation of Six Sigma initiatives. This paper aims to address this issue.Design/methodology/approachThis research adopts a triangulation method, however for the purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
(41 reference statements)
1
35
0
12
Order By: Relevance
“…The Six Sigma methodology can also reduce the complexity of other supply chain performance measurement systems such as Supply Chain Operation Reference Model, which was recommended by the literature (Barber, 2008). As a top-down approach (Klefsjo et al, 2001) and its acquisition and transformation perspectives (McAdam and Hazlett, 2010), business transformation may be required to promote Six Sigma (Al-Mishari and Sulimans, 2008) and the approach is also heavily dependent on the collation and availability of factual and disciplined benchmarking and performance measurement information, training and education, top management commitment and leadership (Suresh et al, 2012;Kumar et al, 2011;Hilton and Sohal, 2012) but the rewards are as developed learning capabilities within managers and employees (Manville et al, 2012), increased customer satisfaction, reduced operation cost, increased revenue and improved processes (Kumar et al, 2006Andersson et al, 2006;Miguel and Anderietta, 2009;Antony and Desai, 2009;Thomas, 2006) although it is recognised as being potentially time consuming and complex (Chakrabarty and Chuan, 2009;Bendell, 2006) and the cost of training and infrastructure can create limitations (Antony, 2006). It was indicated that effective application of Six Sigma can help firms choose their competitive positioning such as focusing on internal efficiencies or differentiation strategies (Malik and Blumenfeld, 2012).…”
mentioning
confidence: 99%
“…The Six Sigma methodology can also reduce the complexity of other supply chain performance measurement systems such as Supply Chain Operation Reference Model, which was recommended by the literature (Barber, 2008). As a top-down approach (Klefsjo et al, 2001) and its acquisition and transformation perspectives (McAdam and Hazlett, 2010), business transformation may be required to promote Six Sigma (Al-Mishari and Sulimans, 2008) and the approach is also heavily dependent on the collation and availability of factual and disciplined benchmarking and performance measurement information, training and education, top management commitment and leadership (Suresh et al, 2012;Kumar et al, 2011;Hilton and Sohal, 2012) but the rewards are as developed learning capabilities within managers and employees (Manville et al, 2012), increased customer satisfaction, reduced operation cost, increased revenue and improved processes (Kumar et al, 2006Andersson et al, 2006;Miguel and Anderietta, 2009;Antony and Desai, 2009;Thomas, 2006) although it is recognised as being potentially time consuming and complex (Chakrabarty and Chuan, 2009;Bendell, 2006) and the cost of training and infrastructure can create limitations (Antony, 2006). It was indicated that effective application of Six Sigma can help firms choose their competitive positioning such as focusing on internal efficiencies or differentiation strategies (Malik and Blumenfeld, 2012).…”
mentioning
confidence: 99%
“…Dessler [10] states that only 15% of the total sample of individuals can be evaluated in the maximum. Recent research reveals the elite diagnostic possibilities according to six sigma principle [11]. Private security personnel selection process should point competency assessment in two directions: external (evaluation of subordinate by his immediate superior) and internal (personal competence) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Organisational learning capabilities, leadership (Antony, 2014;Suresh et al, 2012;and Malik and Blumenfeld, 2012), personal and corporate competence of the project leaders, project team and facilitators (Hilton and Sohal, 2012) and also appropriate technical capabilities (Malik and Blumenfeld, 2012) have been highlighted by the literature as critical subjects to succeed in any LSS project. These subjects can be discovered immensely as academic subjects in the Undergraduate (UG) and Post Graduate (PG) academic curriculums of business schools to develop insightful managers and leaders to deal with business problems.…”
Section: -Business Schools and Lss Knowledge Transfer To Smesmentioning
confidence: 99%
“…Organisational learning capabilities, leadership (Suresh et al, 2012;and Malik and Blumenfeld, 2012), personal and corporate competence of the project leaders, project team and facilitators (Hilton and Sohal, 2012) and also appropriate technical capabilities (Malik and Blumenfeld, 2012) could fit in the analysed modules for both UG and PG levels.…”
Section: Was Clear To Us That Most Of the Final Year Ug And Pg Studenmentioning
confidence: 99%